ANALISIS PENGGUNAAN MEDIA SOSIAL DALAM MITIGASI BENCANA BANJIR DI DKI JAKARTA TAHUN 2020 (Universitas Medan Area, 2021)
This study aims to explain how the use of twitter in disseminating disaster information in order to increase public awareness of natural disasters, namely the twitter account @BPBDJakarta. The research method used is qualitative research with descriptive analysis techniques using Twitter content analysis, one of the government-owned social media accounts using the Nvivo 12 Plus application. In addition, the research also uses data triangulation to obtain the required data. The source is obtained from information from credible online newspapers that have been registered with the press council, so that the information submitted can be justified. The results of this study conclude that the Jakarta Regional Disaster Management Agency's twitter account coordinates all units involved in disaster management. The information posted by BPBD DKI Jakarta on its twitter account is a form of disaster management stages which include pre-disaster (preparedness, early warning and mitigation), during a disaster (emergency response and disaster management), and post-disaster (rehabilitation and reconstruction). The contribution of hastags twitter on the Twitter account of the Jakarta Regional Disaster Management Agency for flood disaster mitigation in this case this Twitter account acts as a government medium to listen to information obtained from # hashtags that often appear on its twitter account.